The disease burden of earlier and late‐onset rheumatoid arthritis on depression and related geriatric syndromes - Keskin Demircan, Sultan; Kahveci, Abdulvahap (Wiley, 2025)
AbstractPurposeThis study aims to compare the prevalence of depression and related geriatric syndromes in earlier‐onset rheumatoid arthritis (EORA) patients, who have experienced prolonged inflammation and medication use, with those with late‐onset rheumatoid arthritis (LORA) patients, who often present with an acute and severe course.MethodsIn this multidisciplinary study, patients with EORA and LORA aged 60 and over who were referred to a tertiary rheumatology clinic underwent a geronto‐rheumatologic evaluation. Muscle mass and handgrip strength, cognitive function, nutritional status, Fried frailty index, fall history, gait speed, depression according to Geriatric Depression Scale and Insomnia Severity Index were recorded. The disease characteristics and geriatric syndromes were compared in the two groups. The regression analysis was used to evaluate the association between depression and related variables.ResultsThe mean age of the 129 patients (F:M ratio = 4.15; comprising 64 EORA and 65 LORA) was 67.42 ± 5.18 years. The prevalence of depression, undernutrition, and frailty was observed in 36.4% (47; 129), 41.08% (53; 129), and 47.3% (61; 129), respectively. Patients with EORA presented with a significantly higher prevalence of female gender (87.7% vs. 73.4%, P = 0.033), depression (47.7% vs. 25.0%, P = 0.006), low gait speed (50.0% vs. 32.8%, P = 0.036) and polypharmacy (83.1% vs. 64.1% vs. P = 0.012) compared to patients with LORA. In the regression analysis, insomnia and undernutrition were significantly related to depression (OR: 3.29; 95%Cl: 1.41–7.69, P = 0.006, and OR: 3.03; 95% Cl: 1.33–7.03, P = 0.010, respectively).ConclusionDepression is more prevalent, particularly in patients with EORA, and is associated with malnutrition and insomnia in patients with RA. Thus, geronto‐rheumatologic evaluation should be taken into account in RA management.
Keywords: Male; Aged, 80 and over; Frailty; Depression; Malnutrition; Nutritional Status; Syndrome; Middle Aged; Arthritis, Rheumatoid; Cost of Illness; Sleep Initiation and Maintenance Disorders; Prevalence; Humans; Female; Age of Onset; Geriatric Assessment; Aged